Structural model of the role of personality traits on physical health mediated by life expectancy and cognitive functions in older women - Jafari, Farah; Ghanifar, Mohammad Hassan; Ahi, Qasem (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the role of personality traits on physical health mediated by life expectancy and cognitive functions in elderly women. Method: The present study is a descriptive-correlational study and was performed by structural equation modeling. The statistical population included all elderly women who referred to the neighborhoods of Tehran between May and June 2021. The research sample consisted of 384 elderly women referring to neighborhoods in Tehran who were selected by voluntary sampling method. Data were collected using the NEO Five Factor Personality Traits Questionnaire (McCurry and Costa, 1980), the Cognitive Rescue Abilities Questionnaire (2013), the Life Expectancy Questionnaire (Hazarousi, 2006) and the Physical Health Questionnaire (Spence, Helmrich). And Perd, 1987). Data were analyzed using correlation coefficient, Pearson correlation matrix, multiple regression and structural equation modeling. Also, all statistical calculations were performed using Lisrel 8.80 and SPSS.22 software. Results: The results showed that standard and non-standard coefficients of the direct path of the hypothetical model from personality traits to cognitive actions (β = 0.48; P